ENTREPRENEURSHIP TRAINING: Learn to Make Patterned Fabrics with High Economic Value - Sugeng Widodo (Jurnal PKM Manajemen Bisnis, 2023)
Improving entrepreneurial skills among the younger generation is key in driving the local economy and promoting economic sustainability. Santri, as an important part of the potential community, often need special guidance to develop their entrepreneurial potential. In this context, this study aims to organize entrepreneurship training that focuses on making patterned fabrics with high economic value for students. The main objective of this activity is to increase students' understanding and entrepreneurial skills in the context of producing high-quality patterned fabrics. We also aim to motivate participants to explore and exploit local potential in creating sustainable economic value. This training is implemented through a series of workshops, hands-on practice in making patterned fabrics, group discussions, and individual assistance. The students receive comprehensive training on entrepreneurial aspects, such as business planning, production management, fabric design, and marketing strategies. They are also encouraged to explore cultural and artistic elements in fabric design, as well as the importance of building a strong brand. Collaboration between participants is promoted to enrich their experience and skills. The result of this activity is an increase in understanding and entrepreneurial skills of the students in making patterned cloth. They have succeeded in creating patterned fabrics with unique designs that reflect local culture, and this has received a positive response from the local community. Apart from that, some of the santri have also started their own small businesses to market the patterned cloth products they produced during the training.